VALIDITY AND PRACTICALITY OF THE EMKONTAN LEARNING MODEL TO IMPROVE CREATIVE THINKING, COLLABORATIVE AND LITERACY ENVIRONMENT OF PROSPECTIVE BIOLOGY TEACHER STUDENTS - Nurwidodo Nurwidodo; Samsun Hadi; Ibrohim Ibrohim; Sueb Sueb (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
The purpose of this study was to analyze the validity and practicality of the EMKONTAN model to increase creativity, collaborative skills and environmental literacy of prospective biology teachers. The method used is descriptive research through observation of the implementation of the EMKONTAN model in learning practice. Observation of the implementation was carried out by involving five learning observers. This research was conducted in the even semester of the 2020/2021 academic year at IKIP Budi Utomo Malang and FKIP University of Muhammadiyah Malang. Involving 80 second semester students through total sampling. The validity aspects studied include content validity, face validity and construct validity. Content validity includes needs analysis and conformity with current knowledge. Face validity consists of the correctness of concepts, principles of measurement, instrument format and language. Construct validity includes rationality of the models, theoretical and empirical support, planning and implementation components of the model, learning environment, assessment and evaluation. While the practicality of the model is obtained from the results of observing the implementation of learning through the application of the EMKONTAN syntax which includes socialization and observation of environmental problems, identification and analysis of environmental problems, action plans for solving environmental problems and integration into conservation, actions for solving environmental problems and integration of conservation, monitoring and evaluating processes and the results of the conservation, monitoring and evaluating processes and the results of the action to solve environmental problems and the integration of KSDA, follow-up plans into PKM based on environmental problems and KSDA. The results of the validity of the EMKONTAN model indicate that the model has content, construct, and facial validity with an average value of <3.7 in the very good category that meet the feasibility to be applied in the learning process. In addition, the results of the practicality of the EMKONTAN model include the implementation of each syntax with an average value of <3.6 in the very good category, student activities with an average value of <85% in the very active category, and the obstacles found, namely the existence of an appropriate alternative solution.Keywords: EMKONTAN model, validity, practicality, creativity, collaborative skills, environmental literacy